Frequency of Repeat Caesarean Section at Tertiary Care Hospital - Rizwana Lakho, Anila Mahmood, Nusrat Lakho, Shoaibunisa, Priya Kumari (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of repeat caesarean sections among women presenting at the tertiary care Hospital. Subjects and Methods: This cross-sectional study was done at the Department of Obstetrics and Gynecology, Shaikh Zaid Women Hospital, SMBBMU Larkana. A total of 345 women older than 18 years with a history of at least one previous caesarean section regardless of gestational age or parity were included. After taking a clinical examination and history, the patients were evaluated according to the frequency of repeated caesarean sections. The data was controlled on a pre-designed proforma, and SPSS version 26 was used for the data analysis. Results: The average age of the patients was 25.83±4.15 years, average gestational age was 35.18+3.38 weeks; and the average parity was 2.09+0.35. Out of 345 cases, 28.7% were urban and 71.3% were rural resident. Most of the cases were booked. Out of all women, 57.1% were obese, and 51.59% had diabetes. The frequency of repeated caesarean sections was observed in 66.96% (231 out of 345) of the women. The frequency of the repeated caesarean sections with respect to maternal age and obesity was statistically significant (p-<0.05), while it was statistically insignificant according to gestational age, residency, booking status, and diabetes (p->0.05). Conclusion: In conclusion, the frequency of repeated caesarean sections was observed to be highly prevalent. Effective implementation of caesarean section reduction efforts may be influenced by the social and cultural context, as well as associated beliefs and behaviours. Keywords: Recurrent, Caesarean section, frequency